2019
DOI: 10.1155/2019/8108503
|View full text |Cite
|
Sign up to set email alerts
|

Jieduan-Niwan Formula Reduces Liver Apoptosis in a Rat Model of Acute-on-Chronic Liver Failure by Regulating the E2F1-Mediated Intrinsic Apoptosis Pathway

Abstract: Acute-on-chronic liver failure (ACLF) is a serious and complicated disease that threatens human health because its pathogenesis is unclear, and the outcome of the current therapies has been less than satisfactory. A national famous doctor of traditional Chinese medicine, Qian Ying, created the Jieduan-Niwan Formula (JDNW), based on his long-term clinical experience. However, despite the good clinical outcome, the biological mechanism by which it works is unknown. In the current study, we established an ACLF ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The level of TNF is related to the severity and prognosis of ACLF [ 41 ]. In our previous study, it has been confirmed that JDNW Formula can reduce inflammatory factors such as TNF- α and IL-6 [ 10 ]. By regulating the pathways or related targets like PI3K/Akt pathway, GSK3, JNK, and AMPK, the cAMP signaling pathway is involved in hepatic physiological and pathological processes, including lipid metabolism, inflammation, oxidative stress, endoplasmic reticulum stress, and hepatocyte apoptosis [ 42 ].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The level of TNF is related to the severity and prognosis of ACLF [ 41 ]. In our previous study, it has been confirmed that JDNW Formula can reduce inflammatory factors such as TNF- α and IL-6 [ 10 ]. By regulating the pathways or related targets like PI3K/Akt pathway, GSK3, JNK, and AMPK, the cAMP signaling pathway is involved in hepatic physiological and pathological processes, including lipid metabolism, inflammation, oxidative stress, endoplasmic reticulum stress, and hepatocyte apoptosis [ 42 ].…”
Section: Discussionmentioning
confidence: 92%
“…According to the network, targets of JDNW Formula for treating ACLF are involved in the responses to oxidative stress, responses to the pathogen-associated molecular pattern (PAMP), regulation of inflammatory responses, apoptotic pathways, and cell proliferation. In fact, our previous study has proved that JDNW Formula can alleviate ACLF by regulating JNK-induced mitochondrial apoptotic pathway and E2F1-mediated intrinsic apoptosis pathway in vivo [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies should discuss therapeutic potential against these diseases before clinical usage. Our previously published data showed that JDNW formula protected liver tissue against human serum albumin (HSA) combined with D-galactosamine (D-GalN) and lipopolysaccharide (LPS)-induced liver failure, decreased mortality and inhibited hepatocyte apoptosis [20]. Therefore, the present study aimed at understanding the biological mechanisms of JDNW formula against liver failure and identi cation of important ingredients of this formula.…”
Section: Discussionmentioning
confidence: 98%